A Longitudinal Investigation of the Associations Among Parenting, Deviant Peer Affiliation, and Externalizing Behaviors: A Monozygotic Twin Differences Design. (10th May 2013) - Hou, Jinqin; Chen, Zhiyan; Natsuaki, Misaki N.; Li, Xinying; Yang, Xiaodong; Zhang, Jie; Zhang, Jianxin
Abstract : Non-shared parenting and deviant peer affiliation are linked to differences in externalizing behaviors between twins. However, few studies have examined these two non-shared environments simultaneously. The present study examined the transactional roles of differential parenting (i.e., warmth and hostility) and deviant peer affiliation on monozygotic (MZ) twin differences in externalizing behaviors using a two-wave longitudinal study of twins and their parents. The sample consisted of 520 pairs of MZ twins (46.5% males, 53.5% females), with a mean age of 13.86 years ( SD = 2.10) at the T1 assessment, residing in Beijing, China. The association between non-shared hostility in parenting and adolescent externalizing behaviors was mainly explained by a child-driven effect whereby the twin with a higher level of externalizing behaviors than his or her co-twin was more likely to receive more hostility from the parents. Similarly, the relationship between deviant peer affiliation and adolescent externalizing behaviors supported the selection effect whereby the twin with a higher level of externalizing behaviors than his or her co-twin was more likely to affiliate with deviant peers. The theoretical and practical implications of these findings are discussed.